Do Social Transfers "Crowd-Out" Remittances: Evidence from Bosnia - Nermin Oruč (The Vienna Institute for International Economic Studies (wiiw), 2011)
This paper presents the results of estimation of the model of interaction between social transfers and remittances. Compared to previous studies, this paper estimates non-monotonic "crowding out" effect by an innovative empirical model specification. The model is then estimated by the two-stage Heckman's selection method, where the receipt of remittances is the first stage, and amount of remittances received second stage dependent variable. The findings suggest that social transfers crowd-in remittances and that the predominant motive for sending remittances to Bosnia is exchange. In addition, the results do not support the Cox (1997) hypothesis about non-monotonic transfer motives.
Keywords: 330